Constraints on the performance of school-based dental program in Yogyakarta, Indonesia: A qualitative study - Rosa Amalia; Niken Widyanti; Johan W. Groothoff; Rob M.H. Schaub (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: A high prevalence of caries at ages ≥ 12 in Yogyakarta province (DMFT = 6.5), raises the question of the effectiveness of the school-based dental program (SBDP) which, as a national oral health program in schools, is organized by community health centers (CHCs). Purpose: The aim of this study is to explore the possible constraints on work processes which might affect the performance of SBDPs in controlling caries. Methods: In-depth interviews was conducted in twelve CHCs, covering all five districts both in urban and rural areas. Subjects were 41 dentists and dental nurses working in these CHCs. The interviews were structured according to the following themes: resources and logistics; program planning; target achievement; monitoring and evaluation; and suggestions for possible improvements. The data were analyzed using content analysis. Results: The main constraints identified were limited resources and inflexible regulations for resource allocation in the CHC, and inadequate program planning and program evaluation. Inadequate participation of parents was also identified. Another constraint is thatpolicy at the district level orientates oral health towards curative intervention rather than prevention. Suggestions from interviewees include encouraging a policy for oral health, task delegation, a funding program using school health insurance, and a reorientation towards prevention. Conclusion: The weakness of management processes and the unsupported policy of the SBDP at the local level result in a lack of effectiveness. The constraints identified and suggestions for improvements could constitute a basis for improving program quality.Latar Belakang: Tingginya prevalensi karies pada usia ≥ 12 tahun (DMFT = 6.5) di Provinsi Daerah Istimewa Yogyakarta (DIY) menimbulkan pertanyaan akan efektifitas Usaha Kesehatan Gigi Sekolah (UKGS). UKGS adalah salah satu program nasional di bidang kesehatan gigi dan mulut yang dilaksanakan oleh Puskesmas. Tujuan: Tujuan dari penelitian ini adalah untuk mengeksplorasi hambatan pada pelaksanaan UKGS yang dapat mempengaruhi kinerja dari UKGS untuk mengontrol karies. Metode: Penelitian kualitatif dengan menggunakan in-depth interview dilakukan di 12 Puskesmas, meliputi lima kabupaten di DIY baik di daerah pedesaan maupun perkotaan. Subyek terdiri dari 41 dokter gigi dan perawat gigi di Puskesmas. Struktur tema dari wawancara adalah sumber daya dan logistik; perencanaan program; pencapaian target; monitoring dan evaluasi; saran untuk perbaikan program. Data dianalisis menggunakan analisis konten. Hasil: Hambatan pada program UKGS yang teridentifikasi adalah sumber daya yang terbatas dan regulasi yang tidak fleksibel untuk alokasi sember daya di Puskesmas, perencanaan dan evaluasi program yang tidak memadai dan rendahnya peran serta orang tua. Hambatan lain adalah kebijakan pada tingkat kabupaten yang berorientasi pada pelayanan kuratif daripada preventif. Saran yang dikemukakan adalah penguatan kebijakan untuk kesehatan gigi, delegasi tugas, asuransi kesehatan sekolah dan reorientasi pelayanan preventif. Kesimpulan: Proses manajemen yang lemah dan kurangnya dukungan kebijakan untuk UKGS pada tingkat daerah menjadi salah satu sebab kurang efektifnya program. Hambatan dan saran yang teridentifikasi pada studi ini dapat menjadi dasar untuk meningkatkan mutu program.